Caloric Restriction Alters Postprandial Responses of Essential Brain Metabolites in Young Adult Mice - Yanckello, Lucille M.; Young, Lyndsay E. A.; Hoffman, Jared D.; Mohney, Robert P.; Keaton, Mignon A.; Abner, Erin; Lin, Ai-Ling (Frontiers in Nutrition, 2019)
Caloric restriction (CR) has been shown to extend longevity and protect brain function in aging. However, the effects of CR in young adult mice remain largely unexplored. In addition to the fundamental, long-term changes, recent studies demonstrate that CR has a significant impact on transient, postprandial metabolic flexibility and turnover compared to control groups. The goal of the study was to identify the brain metabolic changes at a transient (2 hour) and steady (6 hour) postprandial state in young mice (5-6 months of age) fed with CR or Ad Libitum (AL; free eating). Using metabolomics profiling, we show that CR mice had significantly higher levels of neurotransmitters (e.g., glutamate, N-acetylglutamate), neuronal integrity markers (e.g., NAA and NAAG), essential fatty acids (e.g., DHA and DPA), and biochemicals associated carnitine metabolism (related to reduced oxidative stress and inflammation) in the cerebral cortex and hippocampus at 2-hrs. These biochemicals remained at high levels at the 6-hr postprandial time-point. The AL mice did not show the similar increases in essential fatty acid and carnitine metabolism until the 6-hr time-point, and failed to show increases in neurotransmitters and neuronal integrity markers at any time-point. On the other hand, metabolites related to glucose utilization – glycolysis and pentose phosphate pathway (PPP) – were low in the CR mice throughout the 6-hr period and significantly increased at the 6-hr time-point in the AL mice. Our findings suggest that CR induces distinct postprandial responses in metabolites that are essential to maintain brain functions. CR mice produced higher levels of essential brain metabolites in a shorter period after a meal and sustained the levels for an extended period, while maintaining a lower level of glucose utilization. These early brain metabolism changes in the CR mice might play a critical role for neuroprotection in aging. Understanding the interplay between dietary intervention and postprandial metabolic responses from an early age may have profound implications for impeding brain aging and reducing risk for neurodegenerative disorders.